利用非傳統穩定同位素探討前寒武紀/寒武紀過渡期之古環境變化(II) - 游鎮烽 (2018)
計畫編號:MOST107-2116-M006-005 執行機構:國立成功大學地球科學系（所） 2018-08~2019-07 地球歷史與生命演化有著緊密的關聯性。地表環境變遷將導致適合者生存，而較不適者逐漸消亡；同時較具生陳代謝/生物化學優勢能力族群，例如氧氣來源的光合作用，可顯著改變海洋或大氣組成和地表風化。遠古宙至早顯生宙地層，介於埃迪卡拉和寒武紀黑色頁岩層過渡帶，記錄著雪球地球時期劇烈氣候、環境變化和生物演化的資訊。為研究相關地層，我們已組成多專長國際研究團隊(中、台、蘇和美)，進行合作研究，預期可產生整合資料，提供關於埃迪卡拉雪球地球和早期生命快速分異演化的相關過程。 根據SEM初步評估，已經發現數種適合使用於U-Pb定年礦物，並利用雷射剝蝕及SIMS進行初步鋯石或磷釔礦定年，結果證實碎屑礦物對定年結果有關鍵影響。另外，將逐步應用多重同位素系統於重建古環境指標研究；諸如：硼（pH）、硫（生地化循環）、鉬/釩或鈾同位素（還原狀態）、鍶、鈣和鎂（陸源及風化）、和碳、氮、氧（碳源及生物循環）；如有適當磷灰石存在，其結構中REE-取代鈣程度，將可紀錄環境的相對氧氣濃度，配合pH代用指標測量，將可估算遠古宙海洋酸度狀況。本計畫擬重建藍田/甕安雪球地球的海洋環境變遷紀錄，並還原其所含有微體化石在被礦化作用前形貌特性。 此計畫為延續性計畫(II)， 106年度9月中旬我們參與了「寒武紀/前寒武紀過渡帶(II)」國際團隊於中國科技大學舉辦的聯合會(II)，會後前往貴州省貴陽和甕安等地野外勘查，參觀與過渡帶相關磷礦場，並獲得珍貴含磷岩石標本，供後續薄片切割、製造、顯微鏡觀察、雷射剝蝕、SEM或TEM照相或化學成分和多種同位素比值等分析使用；小部分篩選標本目前已利用日本東京大學或中研院地科所NanoSIMS，針對磷灰石及微量磷釔礦或獨居石和鋯石進行微區U-Pb定年，初步獲得年代資料顯示詳細微區觀測是為礦物標地定年的重要前置工作，107年度將利用雷射剝蝕電漿質譜儀針對微區礦物中硫同位素、REEs及微量元素等分部狀況進行精確測量，以期正確解開寒武紀/前寒武紀過渡帶的海洋環境的變化及伴隨生命演化的歷程。 Earth's history and the evolution of life are closely interconnected. Changes in the ambient environment lead to selection of organisms best able to cope with the new settings and a winnowing out of the less adapted. At the same time, the advent of new metabolic/biochemial capabilities –the origin of oxygenic photosynthesis, for example – have greatly influenced the composition of the atmosphere and oceans and the weathering of the land surface. We have established an international-team, including scientists (China, Taiwan, Russia and USA) to tackle various issues in Precambrian/Cambrian transition period and we have been assigned to focus on developing proper U-Pb dating technique for apatite grains or other authigenic minerals, as well as examine other redox sensitive isotopes in the Neoproterozoic Doushantuo and Lantian Formation, South China. Our preliminary SEM studies have documented the occurrence of numerous minerals suitable for U-Pb dating. Initial results using Electron Probe and LA-ICPMS analyses have also identified secondarily emplaced detrital minerals (e.g., zircon) that on the bases of their morphology and/or chemistry can now be excluded from our micro-mineral age determinations. On the other hand, our studies will also focus on environmental proxies, including B isotopes (for oceanic pH); S isotopes (for biogeochemical cycling); Mo, V and U isotopes (for redox and oxygenation conditions); other Sr, Ca and Mg isotopes (for continental weathering); and stable C, N and O isotopes (for carbon sources and productivity). Where present, REE-substituted apatite will document relative oxygen concentrations in the aqueous environment and δ11B pH proxy will provide needed data to estimate Neoproterozoic ocean acidity. This project aims to reconstruct marine environmental changes recorded in Lantian and Weng’an strata on the Snowball Earth and to characterize in detail the permineralized microscopic fossils they contain. Our international team will use state-of-the art techniques to provide new telling data about the evolution of life and the environment on the Snowball Earth. This is a continuous study of "Precambrian/Cambrian Transition Project” to examine in details of the chemical and isotopic variations recorded in the phosphorite specimens collected from the Doushantuo Formation in Guiyang, China. We attended “the Precambrian/Cambrian Transition workshop (II)” held at USTC in mid-September, 2017. After the workshop, we conducted a field work to visit some of the phosphorite mines in Guiyang and have obtained specimens for optical thin sections, LA-ICPMS rock slabs and further SEM & TEM thin sections, as well as powders for wet chemistry on various isotopic and trace elements analyses. A few selected specimens of apatite, xenotime, monazite and zircon grains have been tried to date using NanoSIMS facilities at Tokyo University and IESAS during the second half-year in 2017. The obtained ages are interesting, but emphasizing the importance of sediment diagenetic processes after these minerals buried. These processes can be evaluated using the REEs distribution pattern or other sensitive tracers. In this coming fiscal year, we will apply the available state-of-the-art techniques to gain a better understanding of S isotopes, REEs and other sensitive trace elements migration across the Precambrian/Cambrian transition boundary. 地球科學系 理學院 國科會研究報告